Genotyping and Molecular Characterization of Infectious Bursal Disease Virus Identified in Important Poultry-Raising Areas of China During 2019 and 2020 - Jiang, Nan; Wang, Yulong; Zhang, Wenying; Niu, Xinxin; Huang, Mengmeng; Gao, Yulong; Liu, Aijing; Gao, Li; Li, Kai; Pan, Qing; Liu, Changjun; Zhang, Yanping; et al. (Frontiers in Veterinary Science, 2021)
Infectious bursal disease (IBD) is an acute and highly contagious immunosuppressive disease caused by the infectious bursal disease virus (IBDV), which seriously threatens the healthy development of the poultry industry. Since its spread to China in the early 1990s, the very virulent IBDV (vvIBDV) characterized by high lethality, has been the focus of prevention and control. However, the novel variant IBDV (nVarIBDV), which has been widely prevalent in China since 2017, has brought a new threat to the poultry industry. In this study, the prevalence of IBDV in the important poultry-raising areas of China from 2019 to 2020 was detected. Of these, 45.1% (101/224) of the samples and 61.9% (26/42) of the chicken flocks were shown to be positive for IBDV. For 50 IBDVs, the sequences of the hypervariable region of the VP2 gene in segment A and of the B-marker of the VP1 gene in segment B were analyzed. The results revealed the coexistence of a number of different IBDV genotypes, including A2dB1 (nVar, 26/50, 52.0%), A3B3 (HLJ0504-like, 15/50, 30.0%), A1B1 (classical, 1/50, 2.0%), and A8B1 (attenuated, 1/50, 2.0%). This indicated that the newly emerging nVarIBDV of A2dB1 and the persistently circulating HLJ0504-like vvIBDV of A3B3 are the two important epidemic strains. Furthermore, we established that segment reassortment has occurred among these circulating strains. This study is the first to reveal the novel epidemic characteristics of IBDV since the report of the emerging nVarIBDV of A2dB1 in China.